Asymmetry and changes in the neuromuscular profile of short-track athletes as a result of strength training - Pakosz, P.; Lukanova-Jakubowska, A.; Luszczki, E.; Gnoinski, M.; García-García, O. (PLOS ONE, 2021)
Background: The purpose of this study was to identify the biomedical signals of short-track athletes by evaluating the effects of monthly strength training on changes in their neuromuscular profile, strength, and power parameters of the lower limb muscles. Muscle asymmetry, which can cause a risk of injury, was also evaluated. Methods and results: This study involved female athletes, age 18.8 ± 2.7 years, with a height of 162 ± 2.4 cm, and weight of 55.9 ± 3.9 kg. Before and after the monthly preparatory period prior to the season, strength measurements were assessed through the Swift SpeedMat platform, and reactivity of the lower limb muscles was assessed with tensiomyography (TMG). The athletes were also tested before and after the recovery training period. In the test after strength training, all average countermovement jump (CMJ) results improved. Flight time showed an increase with a moderate to large effect, using both legs (5.21%). Among the TMG parameters, time contraction (Tc) changed globally with a decrease (-5.20%). Changes in the results of the test after recovery training were most often not significant. Conclusion: A monthly period of strength training changes the neuromuscular profile of short-track female athletes, with no significant differences between the right and left lower limbs.